A dedicated caller for DUX4 rearrangements from whole-genome sequencing data - Pascal Grobecker; Stefano Berri; John F. Peden; Kai-Jie Chow; Claire Fielding; Ivana Armogida; Helen Northen; David J. McBride; Peter J. Campbell; Jennifer Becq; Sarra L. Ryan; David R. Bentley; et al. (BMC Medical Genomics)
Abstract Rearrangements involving the DUX4 gene (DUX4-r) define a subtype of paediatric and adult acute lymphoblastic leukaemia (ALL) with a favourable outcome. Currently, there is no ‘standard of care’ diagnostic method for their confident identification. Here, we present an open-source software tool designed to detect DUX4-r from short-read, whole-genome sequencing (WGS) data. Evaluation on a cohort of 210 paediatric ALL cases showed that our method detects all known, as well as previously unidentified, cases of IGH::DUX4 and rearrangements with other partner genes. These findings demonstrate the possibility of robustly detecting DUX4-r using WGS in the routine clinical setting.